Introducing Dewey - Fairfield, Paul, 1966- (London ; New York)
228 sayfa
Keywords: ''This introduction to one of the most influential philosophers in American history examines every major dimension of John Dewey's philosophy, from his early post-Hegelian idealism to pragmatic experimentalism, as well as his views on ethics and political theory, philosophy of education, aesthetics, and philosophy of religion. It situates Dewey's thought in the context of his time (1859-1952) and personal biography while also discussing his considerable work as America's foremost public intellectual through the first half of the 20th century. With a particular focus on how Dewey's thought can be applied to real life and its particular relevance to the contemporary moment, Introducing Dewey is the ideal starting point for anyone with an interest in this seminal figure in American philosophy.'' --